Training and illness characteristics of cross-country skiers transitioning from junior to senior level - Karlsson, Ø.; Laaksonen, M. S.; McGawley, K. (PLOS ONE, 2021)
Objective: This study aimed to describe the endurance training and incidence of illnesses reported by a group of well-trained cross-country (XC) skiers throughout their transition from junior to senior level. Methods: Changes in self-reported training and performance, from 31 well-trained XC skiers, were analyzed from the start of the season they turned 16 y until the end of the season they turned 22 y, using linear mixed-effects models. Differences in the incidence of self-reported illness episodes were analyzed using incidence rate ratios, and the relationships between self-reported illness and training volumes were analyzed using linear mixed-effects models in a sub-group of 23 of the skiers. Results: In total, 145 seasons of training data (including 85,846 h of endurance training) and 109 person-years of illness data (including 380 self-reported illness episodes) were analyzed. The athletes progressively increased their annual endurance training volume from age 16 to 22 y in a linear fashion, from ~ 470 to 730 h. Low- and high-intensity training volumes increased by 51.4 ± 2.4 h·y-1 (p < .001) and 4.9 ± 0.6 h·y-1 (p < .001), respectively. Sport-specific and non-specific training increased by 50.0 ± 2.2 h·y-1 (p < .001) and 4.6 ± 2.0 h·y-1 (p < .001), respectively. The athletes reported a median (range) of 3 (0-8) illness episodes and 17 (0-80) days of illness per year, and there was an inverse relationship between self-reported illness days and annual training volume (-0.046 ± 0.013 d·h-1; p < .001). Conclusions: This group of well-trained XC skiers increased their endurance training volume in a linear fashion by ~ 55 h annually. This was primarily achieved through an increase in low-intensity and sport-specific training. Furthermore, higher training volumes were associated with a lower number of self-reported illness days.